2022
DOI: 10.3390/diagnostics12020373
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Diagnosis of Supernumerary Hemivertebra

Abstract: Hemivertebra is a common cause of congenital scoliosis and results from a lack of formation of one-half of the vertebral body. This condition is very rare and can present as solitary or as a syndrome component: i.e., the split notochord syndrome, which often implies vertebral defects, from a bifid vertebra to hemivertebrae, or fused vertebrae. We describe a case of supernumerary lateral hemivertebra detected prenatally at 12 weeks of gestation and the ultrasonography specifics that lead to early and accurate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…This finding detects as an incidental finding on radiography or post-mortem specimens and does not contribute to neurological signs (Denoix, 2005;Wong et al, 2005). It has been shown that hemivertebra may be associated with other congenital musculoskeletal anomalies including spine, limbs, and ribs malformations, neural tube defects, and extramusculoskeletal anomalies including the cardiac, genitourinary, central nervous system, and gastrointestinal tract anomalies, probably due to anatomically unbalanced growth between hemivertebra and structural differentiation of surrounding spine (Bohiltea et al, 2022;Chaturvedi et al, 2018;Moser, 2005;Varras & Akrivis, 2010;Yang et al, 2020). Because the structure of the ribs is formed in close association with vertebrae during gestation, the same developmental failures that lead to hemivertebra are attributed to rib abnormalities (Fischer & Degenhardt, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This finding detects as an incidental finding on radiography or post-mortem specimens and does not contribute to neurological signs (Denoix, 2005;Wong et al, 2005). It has been shown that hemivertebra may be associated with other congenital musculoskeletal anomalies including spine, limbs, and ribs malformations, neural tube defects, and extramusculoskeletal anomalies including the cardiac, genitourinary, central nervous system, and gastrointestinal tract anomalies, probably due to anatomically unbalanced growth between hemivertebra and structural differentiation of surrounding spine (Bohiltea et al, 2022;Chaturvedi et al, 2018;Moser, 2005;Varras & Akrivis, 2010;Yang et al, 2020). Because the structure of the ribs is formed in close association with vertebrae during gestation, the same developmental failures that lead to hemivertebra are attributed to rib abnormalities (Fischer & Degenhardt, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The latter include abnormalities of the heart, genitourinary system, central nervous system and gastrointestinal tract. These other lesions may arise due to anatomically unbalanced growth as a consequence of the hemivertebra and associated abnormalities in structural differentiation of tissues surrounding the vertebral column (Bohiltea et al, 2022; Chaturvedi et al, 2018; Moser, 2005; Varras & Akrivis, 2010; Yang et al, 2020). As the ribs develop closely with vertebrae during gestation, the same developmental failures that lead to hemivertebrae are attributed to rib abnormalities (Fischer & Degenhardt, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that fetal vertebral malformation arises in the early stage of pregnancy, but X-ray irradiation and other examination methods cannot be used at this stage of pregnancy due to radiation risks and other reasons, it is of great clinical significance to develop an accurate and easy marker for the early diagnosis of CS. [ 30 , 31 ] However, due to the lack of maternal peripheral blood or umbilical cord blood samples taken during pregnancy, it is impossible to know at this point whether the levels of FGF23 mRNA in the maternal blood change during pregnancy when CS is present in the fetus. Therefore, whether the levels of FGF23 mRNA can be used for the early diagnosis of patients with CS needs further study.…”
Section: Discussionmentioning
confidence: 99%